Perspective of passive IR imaging using in energetic and manufacture - Vavilov V. P. Vladimir Platonovich; Demin V. G.; Shiryaev V. V.; Nesteruk D. A. (2003, 2003)
The aim of the is to analyze the prospects for using the passive IR imaging monitoring in the power engineering and industry. The fields of application of the IR imaging for checking the heat shields of building structures, chimney stock monitoring, boilers, cooling ponds and thermal lines are considered.